Topological Descriptors and QSPR Modelling of HIV/AIDS Disease Treatment Drugs - Fozia Bashir Farooq; Saima Parveen; Nadeem Ul Hassan Awan; Rakotondrajao Fanja (Discrete Dynamics in Nature and Society)
A topological index is a real number derived from the structure of a chemical graph. It helps determine the physicochemical and biological properties of a wide range of drugs, and it better reflects the theoretical properties of organic compounds. This is accomplished using degree-based topological indices. We examined some of the physiochemical characteristics of thirteen HIV therapy medications and created a QSPR model utilizing nine of the medication’s topological indices. The melting point, boiling point, flash point, complexity, surface tension, etc., of HIV medicines are closely related according to this QSPR model. This work can help to design and synthesize new HIV treatments and other disease drugs.